(untitled) (International Journal of Nursing Education, 2019)
Background of the Study: Indian families are undergoing rapid changes due to the increased pace of urbanization and modernisation. Indian women belonging to all classes have entered into paid occupations. Stress is a complex and highly personalized process. As such, stress levels in individuals can vary widely, even in identical situations, due to women’s abilities to cope with different forms and levels of stress. Methodology: A cross sectional research design was adopted for the study. Purposive sampling technique was adopted to select 200 working women from selected institutions in Mangaluru. Married women belonging to nuclear families, willing to participate and present at the time of data collection were included in the study. Three tools were used to collect information from working women namely demographic variables with 10 items, Singh Personal Stress Source Inventory and the Coping Scale. Ethical clearance was obtained from A.J. Ethics Committee. Permission was obtained from the concerned authorities as well as the working women. Analysis was done by using descriptive and inferential statistics. Results: The findings revealed that majority (91.5%) of the working women’s had moderate stress, and least percentage (8.5%) of the working women’s had high stress. None of the working women has low stress. The majority (95%) of the working women has average coping and least percentage (5%) has good coping. There is significant association of level of stress and coping with demographic variables such as age, presence of maid at home, mode of transport to the work place. Interpretation and Conclusion: The study concludes that majority of the working women had moderate stress level and had average coping The study provides valuable insight into the stressful experience and the use of coping strategies adopted by working women.